Income Analysis of Kalang Buffalo Farmers in the Tanjung Terakan Group Kutai Kartanegara Regency - Kharidha Armina; Dinar Anindyasari; Ibrahim; Suhardi; I Putu Gede Didik Widiarta; Ardiansyah; Ruth Dameria Haloho (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2024)
Buffalo farming is an integral part of Indonesia's agricultural system, particularly in the Tanjung Terakan group, Muara Wis District, Kutai Kartanegara Regency. Small-scale farmers in this area raise kalang buffaloes as a secondary enterprise, utilizing family labor. This study aims to assess the profitability and performance of buffalo farming in this region. The research employed a survey method to gather data on production costs and income of the farmers. The findings revealed that the average annual income of the Tanjung Terakan group is IDR 134,549,211.00, with a remarkable profit margin of 2,247%. Despite a 9% yearly interest rate charged by Bank Kaltimtara, the buffalo business in this area remains lucrative. Based on these results, it is recommended that the Tanjung Terakan group continue their buffalo farming efforts due to the significant value it brings.